Social class, the elite hockey player career and educational paths - Moret, O.; Ohl, F. (International Review for the Sociology of Sport, 2019)
This paper focuses on how engaging in hockey as an elite athlete influences educational paths. It relies on qualitative and quantitative methods, including interviews with 36 ice hockey players in Switzerland and 605 respondents who completed a questionnaire. We argue that a strong family belief in sport capital predisposes athletes to leave school early, for both the lower- and upper-middle classes. For families with more economic capital, leaving school is a strategy for maintaining or improving social positioning; for lower-middle-class families, it is driven more by the individual opportunities provided by sporting talent. Regardless of class, players with families that are more sensitive to scholastic culture favour schooling as a resource for athletes` transition to another professional career. However, the over-valorization of sport capital does not have the same consequences for both classes. Players with fewer social resources, who believe that the social capital related to sport will enable their transition, are more at risk than those who have families that can support them owing to their economic and cultural resources. In addition, the recent globalization of hockey seems to further increase inequalities and to weaken the strength of local networks. Finally, the results suggest paying more attention to both beliefs and contexts, as well as the Weberian influence on Bourdieu`s research, when studying the role of the various forms of capital in decision-making concerning education.